Analysis of Heat Transfer on film cooling performance in a flat plate. (February 2019) - Tan, Xiaoming; Zhou, Xiaoming; Shan, Yong; Zhang, Jingzhou
Abstract: Realizable k-ε turbulence model and Enhanced Wall Treatment were used to investigate film cooling performance in a flat plate. The effect of length-diameter ratio, blowing ratio and film cooling hole angle on the heat transfer coefficient were analyzed individually. The results show that the overall average convective heat transfer coefficient of film cooling hole increased with the decrease of length-diameter ratio, the increase of blowing ratio and film cooling hole angle; the area of enhanced convective heat transfer is increased in the cold side of the plate with the increase of length-diameter ratio and blowing ratio; Increasing blowing ratio leads to the reduce of convective heat transfer coefficient of the same position on hot side. The decrease of film cooling hole angle aggrandizes the film covered region on hot side of the plate.